Cross-border sovereign risk transmission in BRICIT Nations: Unveiling asymmetries and the role of country risk premiums - Pawan Kumar; Vipul Kumar Singh (Borsa İstanbul Review, 2024)
This research highlights the asymmetric interdependence structure among the sovereign risks of Brazil, Russia, India, China, Indonesia, and Türkiye (BRICIT) nations, challenging the traditional view that bilateral trade is the main channel for cross-border spillover effects. Despite their dependence on Russian crude oil imports for energy, the BRICIT nations show no significant sovereign risk interdependence with Russia. The study finds that Indonesia's credit default swap (CDS) has the highest level of interdependence with other nations. Further exploration of alternative transmission channels necessitates an examination of the country risk premium, revealing Türkiye as the most vulnerable nation due to its negative association with the CDS of other countries, particularly India. By contrast, India is identified as a preferred investment destination, thanks to its lower uncertainty and strong GDP growth over the past decade. Additionally, the research underscores China's economic influence, demonstrated by its positive association with all other BRICIT nations. This suggests that despite the high sovereign risk associated with China, investors do not view other emerging markets as viable, lower-risk alternatives. The perceived risk related to China appears to extend beyond its borders, impacting the sovereign risk profiles of other emerging economies.
Keywords: F34; F36; F65; G01; G15; 330; BRICIT nations; Country risk premium; Credit default swaps; Interdependence; Sovereign risk